Prevalence and Risk Factor Analysis of Anemia in Pregnancy - Rizki Nur Azmi; Sri Wulandari (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Anemia is a condition in which the total amount of iron in the body is reduced. If iron deficiency is severe enough it can cause interference with the reproduction of red blood cells and cause anemia. This condition will cause weakness, become obstacles to activity and will also hinder the growth and development of children. This research aims to describe prevalence of anemia during pregnancy and determine the risk factors that can influence it. This research is included in the analytic descriptive study using a cross-sectional approach design. The target was pregnant women who had an examination at the Hasanah Clinic in September-November 2022. The data were collected by face-to-face interviews and information in medical record. The results showed that 15% of pregnant women had mild anemia and all predicted risk factors did not significantly influence anemia, such as gestational age (p value 0.074), number of gravidity (p value 0.495), and mid-upper arm circumference (p value 1.000). The provision of iron supplements and good nutritional intake can be one of the efforts to prevent and overcome anemia in pregnant women which develops worse